Primary and Secondary Crystallization Kinetic Analysis of Poly(Hexamethylene Succinate) - Zhiyong Wei (Journal of Advanced Thermal Science Research, 2015)
Isothermal crystallization kinetics of poly(hexamethylene succinate) (PHS) were investigated by using differential scanning calorimetry (DSC). Primary and secondary crystallization behaviors were described satisfactorily by a modified Avrami model. The obtained results suggest that primary crystallization under isothermal conditions involves three-dimensional spherulite growth with athermal nucleation, and secondary crystallization displays approximate one-dimensional crystal growth.